Sustaining the motivation of quantity surveyors in facing the competitive environment - Herman, Siti Sarah (Universiti Putra Malaysia Press, 2019)
The construction industry is complex and is frequently associated with occupational stress. Following this, the employees’ motivation is important as it affects job performance. Motivated employees tend to be better at their jobs as they find and create initiatives to achieve their goals. In the construction industry, quantity surveyors are highly involved in the contractual and financial management of projects. The increasingly challenging environment has changed their work method, causing various significant impacts on performance. This paper explored the impact and effectiveness of motivation on quantity surveyors from three types of organisations in Malaysia; government agencies, private consultancy firms, and private contracting firms. A mixed-methodology was adapted, which included questionnaire surveys and a semi-structured interview with quantity surveyors registered with the Board of Quantity Surveyors Malaysia (BQSM). The findings demonstrated that ‘good relations amongst staff and management team’ sparked motivation the most, reflecting that it is the most effective motivational practice in many organisations.